Realism and Christian faith : God, grammar, and meaning - Moore, Andrew (Cambridge, UK ; New York : Cambridge University Press, 2003)
The author challenges recent understandings of the relationship between science and Christianity and argues for a conception of realism according to which God's independent reality is shown principally in Christ and, on this basis, through Christian practices and the lives of Christians.
Realism and Christian faith : towards an ontological approach -- 'Limping with two different opinions'? -- Taking leave of theological realism -- Realism and Christian faith after Wittgenstein -- The grammar of Christian faith and the relationship between philosophy and theology -- Representation, reconciliation, and the problem of meaning -- God, reality, and realism -- Speaking the reality of God -- Realism : conformed to the conforming Word.
Includes bibliographical references (pages 240-261) and indexes.
Print version record.
Master record variable field(s) change: 082
Keywords: God -- Proof, Ontological; Language and languages -- Religious aspects -- Christianity; Dieu -- Existence -- Preuve ontologique; Langage et langues -- Aspect religieux -- Christianisme; RELIGION -- Christian Theology -- General; God -- Proof, Ontological; Language and languages -- Religious aspects -- Christianity; Christendom; Realisme (filosofie); Taal; Gottesbeweis; Electronic books